Implementasi Pendistribusian Wakaf Tunai Sebagai Penunjang Usaha Kecil Menengah di Badan Wakaf Uang & Badan Wakaf Tunai MUI Yogyakarta - Khurun'in Zahro'; Mulyono Jamal; Jarman Arroisi; Nia Puji Agustin (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2019)
The number of poor people in Indonesia has continued to increase since the economic crisis in 1997 to the present. Population growth below the poverty line is not due to the problem of natural wealth that is not balanced with the population, but is caused by problems of income distribution and unfair economic access. Optimization of Islamic financial resources can be applied to reduce poverty levels. The distribution of cash waqf funds has an important role as one of the capital in developing the economy. Cash Waqf is also able to have a good impact on poverty alleviation. This study aims to determine the implementation of the distribution of cash waqf as supporting the improvement of Small and Medium Enterprises (SMEs). This study uses qualitative methods by using a field survey research design. The results of this study conclude that the implementation of the distribution of good and directed cash waqf can increase mauquf alaihi income and can support the development of SMEs so that it is more productive.